2001
DOI: 10.1021/ci000134w
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Quantitative Structure−Property and −Activity Relationships

Abstract: The potential utility of data reduction methods (e.g. principal component analysis) for the analysis of matrices assembled from the related properties of large sets of compounds is discussed by reference to results obtained from solvent polarity scales, ongoing work on solubilities and sweetness properties, and proposed general treatments of toxicities and gas chromatographic retention indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 54 publications
0
69
0
1
Order By: Relevance
“…3 Recently we have commenced a general analysis of these issues using a combination of chemometric techniques such as multilinear regression analysis (MLR) and principal component analysis (PCA). 4 Our earlier efforts to use PCA to explain physicochemical phenomena have been successful. In an application of the PCA method to a chemical problem, we treated aromaticity as a multidimensional entity and found that the magnetic and structural components are orthogonal.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recently we have commenced a general analysis of these issues using a combination of chemometric techniques such as multilinear regression analysis (MLR) and principal component analysis (PCA). 4 Our earlier efforts to use PCA to explain physicochemical phenomena have been successful. In an application of the PCA method to a chemical problem, we treated aromaticity as a multidimensional entity and found that the magnetic and structural components are orthogonal.…”
Section: Introductionmentioning
confidence: 99%
“…Mesmo que a não interpretação de um modelo não impeça sua utilização para fins de predição, caso seja possível interpretá-lo, reforça a utilidade da equação obtida para explicar o problema em estudo. 23,[41][42][43][44] Outro fato importante a ser considerado neste estudo é que o mecanismo de ação dos compostos estudados contra o P. falciparum 3D7 não é conhecido. Assim, a interpretação mecanística pode ser baseada apenas nos descritores moleculares selecionados, seus significados gerais e por comparação com os resultados de outros estudos QSAR.…”
Section: Figura 4 Resultados Dos Estudos De Validação Cruzada Lno (Aunclassified
“…(Katritzky et al, 2001), as it does not impose any restriction on the type and number of graphical invariants used in structureproperty-activity studies. For a valid statistical significance of the MRA, it is necessary to restrict the maximal number of descriptors, which depends on the number of compounds investigated (Rao, 1973;Randic, 2001) To avoid ambiguities in the interpretation of regression, only a few parameters, or ideally a single parameter, may be used.…”
Section: Discussionmentioning
confidence: 99%